Maximization of the output power of low concentrating photovoltaic systems by the application of reflecting mirrors - Kolamroudi, Mohammad Karimzadeh; Ilkan, Mustafa; Egelioglu, Fuat; Safaei, Babak (Pergamon-Elsevier Science Ltd, 2022)
Solar energy is among the most commonly used sources of renewable energy since sun is available for a significant portion of the year in most parts of the world. Energy from sun can be harnessed through several technologies with continuous progress and development. Concentrated solar power systems apply mirrors or lenses as well as solar tracking systems for the concentration of a large solar radiation area into a tiny PV area. Due to high price of solar panels, several efficiency enhancement methods are being evaluated by researchers throughout the world. In this research, a form of solar technology, i.e. photovoltaic system, was applied to present developed low concentrator photovoltaic system (LCPVS) with cooling. This project aimed to determine how solar panel power output was changed by the application of mirrors to concentrate solar radiation; which they had concentration onto panel for increasing power output from 1 to 4 mirrors with the cooling system. In fact, the aim was to increase the output power by enhancing the amount of solar radiation which reaches the same surface area of solar panel via mirrors. Furthermore, application of mirrors saves PV area which is more economical. Also, the results were compared to a reference solar panel for determining how to increase the power output of a single panel (normal panel receiving solar radiation directly). The results showed that the value of the DC current (A) output of the four mirrors reflecting on the panel is three times greater than that of the reference panel, and the DC power (W) is almost three times greater than the reference panel's power. (c) 2022 Published by Elsevier Ltd.
Keywords: LCPV System; Solar radiation; Output power; Solar panel; Mirrors; Cooling